OCEAN CURRENT MAPPING USING COPERNICUS MARINE DATA IN THE TOGEAN ISLANDS WATERS (CASE STUDY 2021-2022) - Rosalina, Dwi; Rizkiah, Riza; Handayani, Endy; Sulistiyo, Budi; Ismail, R. Moh.; Wardono, Suko; Yusuf, Muhammad; Sabilah, Anisa Aulia (Jurnal Segara, 2025)
The Togean Islands, located in Tomini Bay, Central Sulawesi, Indonesia, are part of the coral triangle that encompasses the waters of Indonesia, the Philippines, Malaysia, Papua New Guinea, Japan, and Australia. This region hosts a coral reef ecosystem that relies on ocean currents for nutrient distribution and coral larval dispersal. Maintaining the balance and health of ocean currents is crucial for the sustainability of this ecosystem. This study aims to map ocean current patterns in the waters of the Togean Islands during the 2021–2022 period using data from Copernicus Marine. A secondary data analysis with a descriptive approach was employed. Data were obtained from the Copernicus Marine platform and processed using SeaDAS and ArcGIS software. In 2021, the recorded current speed was relatively lower, ranging from 0.04 m/s to 0.16 m/s, whereas in 2022, the current movement was stronger, with an average speed ranging from 0.06 m/s to 0.21 m/s. The comparison of ocean currents in the Togean Islands showed peak values in December for both years, while the lowest average speeds were recorded in March 2021 and October 2022. These current patterns are influenced by seasonal factors and play a significant role in marine ecosystem dynamics. This mapping is expected to serve as a reference for the management and conservation of coral reefs in the Togean Islands.